Plant distribution, ecological traits and diversity patterns of vegetation in subtropical managed forests as guidelines for forest management policy - Waheed, Muhammad; Haq, Shiekh Marifatul; Arshad, Fahim; Bussmann, Rainer W.; Hashem, Abeer; Abd_Allah, Elsayed Fathi (Frontiers in Forests and Global Change, 2024)
Forest vegetation is an important component of forest ecosystems, contributing to terrestrial plant diversity while also providing a variety of ecological services. In managed landscapes, plantations emerge as dominant kinds after stand-replacing disturbances. However, the dynamics of vegetation cover, diversity, and composition in plantation forests remains poorly understood in the subtropical region. Our study recorded a rich floral diversity with 173 angiosperm species, characterized by varying life forms and distinct flowering phenology. The uneven distribution of species across families demonstrated the complexity of the ecosystem, with Poaceae being dominant. Diversity patterns among different plantation types varied, with Dalbergia sissoo and Populus nigra plantations exhibiting higher species richness and diversity. Conversely, Eucalyptus camaldulensis and Morus alba plantations displayed lower diversity, emphasizing the influence of plantation type on biodiversity. Non-metric multidimensional scaling (nMDS) and PERMANOVA analyses revealed significant dissimilarity patterns of vegetation composition. Indicator species analysis identified unique compositions within each plantation type, emphasizing the importance of conserving specific types to protect indicator species and maintained ecological distinctiveness. Canonical Correspondence Analysis (CCA) demonstrated that road accessibility, stem cutting, and fire significantly influenced plant distribution patterns. The present research underscored the importance of considering plantation type in forest management for biodiversity conservation and highlighted the environmental variables’ influence on the formation of plant communities. These results provided major implications for sustainable forest management and conservation efforts in tropical regions.